The Gini out of the bottle. An interview with Branko Milanovic - Planel, Niels; Milanovic, Branko (Sens public, 2011)
Branko Milanovic is one of the leading world specialists on inequality. An economist at the World Bank, he’s been dealing with issues related to income distribution for decades. In a book published this year, The Haves and the Have-Nots, he manages to make complex ideas about inequalities within individuals, nations and globally accessible to a wide audience. In it, his essays on these topics are illustrated by audacious and very original « vignettes » in which he answers fascinating and diverse questions such as: Were affluent Romans comparatively richer than today’s super riches? Does the place where you are born influence the revenue you will generate over a lifetime? What did Anna Karenina get for falling in love? Will China survive by the mid-century? Who has the richest person in the world been? Feeding his reflections with the findings of Vilfredo Pareto, Karl Marx, Alexis de Tocqueville, John Rawls or Simon Kuznets at a time when the issue of inequality has become so important, his book enlightens us on a topic that is both ancient and captivating. Branko Milanovic has answered Sens Public’s questions.